'Christ-Faith' as an Eschatological Event (Galatians 3.23-26): A 'Third View' on Πίστις Χριστοῦ1. (March 2016) - Schliesser, Benjamin
The meaning of πίστις Χριστοῦ in Paul (Gal. 2.16, 20; 3.22; Rom. 3.22, 26; Phil. 3.9) continues to be the subject of controversial debate in Pauline scholarship. Should the genitive construction be understood objectively as 'faith in Christ' or subjectively as 'the faith(fulness) of Christ'? The prevalent either/or character of the discussion is increasingly proving to be an impediment to finding a solution to this issue. A minority view, the so-called 'third view', seeks to move beyond the subjective-objective dichotomy by accounting for the intrinsic complexity of the Greek genitive and pointing to the event-character of πίστις in Paul. The primary reference text for this 'third view' is Gal. 3.23-26, which exhibits an altogether remarkable language of faith and envisages πίστις as 'coming' (ἔρχεσθαι) and as 'being revealed' (ἀποκαλύπτεσθαι). This article reviews the exegetical status quaestionis and argues that Paul does not regard πίστις Χριστοῦ as an individual disposition or character (either Christ's or that of the believer), but rather as an eschatological event. The aim is not to offer a comprehensive analysis of the verses in question, but to advance exegetical and theological support for the 'third view' and to point to its considerable explanatory power in our effort for a more nuanced appreciation of Paul's language of faith.